Neogene exhumation history of the Mont Blanc massif, Western Alps - Glotzbach, C.; Reinecker, J.; Danišík, Martin; Rahn, M.; Frisch, W.; Spiegel, C. (American Geophysical Union (AGU), 2008)
The contribution of climate and tectonics to the Neogene exhumation history of the European Alps is studied in the Mont Blanc (MB) massif using low-temperature thermochronology. Apatite fission track and (U-Th-[Sm])/He data suggest that the MB massif was exhumed episodically: Rapid exhumation (2.5 ± 0.5 km/Ma) before 6 Ma is followed by an episode of slow exhumation and a period of accelerated exhumation (>1 km/Ma) after ~3 Ma. Comparing the exhumation rates of the MB massif with reported exhumation rates of all other external crystalline massifs (ECM) shows that the MB massif is the only ECM that experienced rapid exhumation before 6 Ma, which is possibly related to NW and minor SE directed thrusting of the MB massif. The data demonstrate that the Messinian base level drop (~5.5 Ma) and the increase in atmospheric moisture caused by an intensification of the Atlantic Golf Stream (4.6 Ma) did not affect the exhumation of the external Alps. All ECM, except the Gotthard massif, show an increase in exhumation rates at ~3 Ma. We interpret this as the result of normal faulting along orogen-parallel faults and beginning Alpine glaciation. The relative impact of these processes on the exhumation of the ECM can vary spatially and temporally, mainly depending on differences in geology and geomorphology. In the case of the MB massif we propose that the acceleration in exhumation rates at ~3 Ma is caused by rapid valley incision related to glaciation, and that the recent relief of the MB massif is thus a young feature.